2022
DOI: 10.2340/actadv.v102.1991
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disorders and Psoriasis: An Update

Abstract: Psoriasis alters patients’ quality of life. Among the disorders associated with psoriasis, sleep disorders are common, although they are not directly assessed by most quality-of-life scores. Thus, their specific evaluation with dedicated scores is necessary, especially because such disorders alter physical and psychological health. The relationship between psoriasis and sleep disorders has not yet been fully elucidated, but numerous studies in the literature show links between the two. Our study aims to update… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 141 publications
3
25
0
Order By: Relevance
“…Similar studies have been performed regarding sleep quality and other skin conditions, such as psoriasis [ 9 , 15 ]. Interestingly, in these cases, a significant correlation was found between the severity and symptoms of the disease (pain, tender points), as well as subjective wellness (visual analogue scale) and sleep quality indicators.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Similar studies have been performed regarding sleep quality and other skin conditions, such as psoriasis [ 9 , 15 ]. Interestingly, in these cases, a significant correlation was found between the severity and symptoms of the disease (pain, tender points), as well as subjective wellness (visual analogue scale) and sleep quality indicators.…”
Section: Discussionmentioning
confidence: 62%
“…On the other hand, insomnia and sleep disorders are frequent among the general population [ 5 ] and have been associated with a variety of cardiovascular [ 6 ], neurologic [ 7 ] or psychiatric [ 8 ] complications. Moreover, a worse sleep quality has been described in a variety of chronic skin diseases such as psoriasis [ 9 ], atopic dermatitis [ 10 ] or chronic spontaneous urticaria [ 11 ]. In this regard, recent studies [ 12 ] identify a complex interplay among various physiological, psychosocial and behavioral factors mediating the relationship between sleep loss and chronic inflammatory skin diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Although the high prevalence of sleep disturbance in patients with psoriasis has been previously evidenced, and two systematic reviews and a recent update were performed, 2–4 dermatologists are poorly aware of this comorbidity. In a large study, we also showed that sleep disorders were very frequent in patients with inflammatory skin diseases, including psoriasis 5 .…”
Section: Figurementioning
confidence: 99%
“…The role of non-inflammatory conditions like obstructive sleep apnoea and restless leg syndrome has been previously suggested. 4 The presence of inflammatory mediators, like TNFa or substance P, in the blood and consequently the brain of psoriasis patients could also directly favour sleep disorders in these patients. 4 Hence, several factors could be involved (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation